Behavioral analysis of habit formation in modern slot machine gambling. Issue 2 (4th May 2022) - Ferrari, Mario A.; Limbrick-Oldfield, Eve H.; Clark, Luke
ABSTRACT: Habit formation is a key process in contemporary models of addictive behaviors but has received limited attention in the context of gambling and problem gambling. Methods for examining habit formation and expression in relation to gambling are also lacking. In this study, 60 participants with no prior slot machine experience attended three sessions spaced 6–8 days apart, during which they played a short 200-spin session on a realistic simulation of a modern multi-line slot machine. Behavioral data were analyzed to characterize habit formation within and between sessions. Fixed-effects regressions, integrating trial- and session-level effects, assessed predictors of gambling speed (spin initiation latencies) and betting rigidity (the likelihood of switching the bet amount), as two putative markers of habit formation. Participants gambled faster and showed less variability in betting strategy as they accumulated experience in the number of trials and sessions gambled. Simultaneously, as the number of sessions gambled increased, participants showed a more pronounced tendency to slow their betting after larger wins (i.e. the post-reinforcement pause increased from session 1 to session 3). Our methods provide a basis for future research to examine habits in the context of slot machine gambling.